Glutathione contributes to the efflux of selenium from hepatoma cells. Issue 8 (3rd August 2014) - Imai, Takeshi; Kurihara, Tatsuo; Esaki, Nobuyoshi; Mihara, Hisaaki
Abstract: Selenite is a selenium source for selenoprotein biosynthesis in mammalian cells. Although previous studies have suggested the involvement of glutathione (GSH) and/or thioredoxin reductase in selenite metabolism, intracellular selenite metabolism remains largely unknown. Here, we report that GSH depletion did not affect the amount of selenoprotein in Hepa 1–6 cells, suggesting that GSH does not play a central role in the reduction of selenite in selenoprotein biosynthesis. On the other hand, we found that GSH is involved in the efflux of low-molecular-weight selenium compounds from cells, presumably via the formation of selenodiglutathione. Moreover, selenite inhibited the efflux of a fluorescent bimane-GS conjugate that is mediated by ATP-dependent multidrug-resistant proteins, implying the existence of an active transporter for selenodiglutathione. This is the first report demonstrating that GSH plays a role in selenium excretion from cells by forming a GSH-conjugate, which may contribute to the distribution, detoxification, and homeostasis of selenium in the body. Graphical abstract: : Selenite is used for selenoprotein synthesis, whereas excess selenite is effluxed from cells via MRP in the form of GSSeSG to regulate intracellular selenium homeostasis.